Rekonstruksi Hadis-Hadis Akhlak dalam Kitab Waṣāyā al-Ābā’ li Abnā’ dan Relevansinya terhadap Pembentukan Akhlak di Era Kontemporer - Ilsan, Muhammad; Nasution, Hasan Bakti; Siregar, Muhammad Habibi (JOURNAL OF QUR'AN AND HADITH STUDIES, 2024)
This research aims to review the reconstruction of moral hadiths in the book Waṣāyā al-Ābā’ li Abnā’ by Muhammad Syakir and their relevance to the formation of morals in the contemporary era. The method applied is library research with a content analysis approach. The results show that Waṣāyā al-Ābā’ li Abnā’ is a source of lessons about various aspects of morals, including morals towards Allah, teacher's advice to students, morals in worship, and Sufism. This book provides solid moral guidance, building the foundations of the daily lives of Muslims by teaching values such as patience, humility, honesty, and compassion. The relevance of moral hadiths in this work includes character formation, where moral teachings become a solid basis for developing commendable qualities in Islam.